2015
DOI: 10.1038/onc.2015.281
|View full text |Cite|
|
Sign up to set email alerts
|

Stat3 regulates ErbB-2 expression and co-opts ErbB-2 nuclear function to induce miR-21 expression, PDCD4 downregulation and breast cancer metastasis

Abstract: Membrane overexpression of the receptor tyrosine kinase ErbB-2 (MErbB-2) accounts for a clinically aggressive breast cancer (BC) subtype (ErbB-2-positive) with increased incidence of metastases. We and others demonstrated that nuclear ErbB-2 (NErbB-2) also plays a key role in BC and is a poor prognostic factor in ErbB-2-positive tumors. The signal transducer and activator of transcription 3 (Stat3), another player in BC, has been recognized as a downstream mediator of MErbB-2 action in BC metastasis. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 80 publications
(140 reference statements)
2
51
0
1
Order By: Relevance
“…57 Our own findings demonstrated that ErbB-2 nuclear function as a coactivator of Stat3 and as a transcription factor are mandatory for miR-21 upregulation. 58 Interestingly, several of the tumor types which, in addition to BC and GC, show ErbB-2 gene amplification or protein overexpression, display low levels of miR-16. 5965 Given that miR-16 was found to act as a tumor suppressor in these cancers, 5965 our findings raise the exciting possibility that ErbB-2 inhibition of miR-16 expression may be a common mechanism underlying ErbB-2-driven cancer growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Our own findings demonstrated that ErbB-2 nuclear function as a coactivator of Stat3 and as a transcription factor are mandatory for miR-21 upregulation. 58 Interestingly, several of the tumor types which, in addition to BC and GC, show ErbB-2 gene amplification or protein overexpression, display low levels of miR-16. 5965 Given that miR-16 was found to act as a tumor suppressor in these cancers, 5965 our findings raise the exciting possibility that ErbB-2 inhibition of miR-16 expression may be a common mechanism underlying ErbB-2-driven cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcriptase (RT)–quantitative PCR (qPCR) was performed as described. 58 Details are provided in Supplementary Materials and methods.…”
Section: Methodsmentioning
confidence: 99%
“…STAT3 co-opts the function of nuclear HER2 by recruiting it as its co-activator at the response elements in the promoter of miR-21. miR-21, in turn, was found to downregulate the expression of the metastasis suppressor protein PDCD4 in breast cancer (52). Further studies disclosed that serum and urine miR-21 may be a potential diagnostic biomarker for breast cancer; however, prior to its implementation in the clinic, further investigation is warranted (53,54).…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
“…microRNA 21, also known as hsamir-21 or miRNA 21 is encoded by the miR-21 gene located on chromosome 17q23.2 immediately downstream of the vacuole membrane protein-1 (VMP1) gene [4,6]. miR-21 is a common microRNA that is upregulated in a wide variety of cancers, including breast [13] ovaries [14] cervix [15] colon [16] lung [17] and liver [18]. In addition, it has been identified that miR-21 is consistently upregulated in several types of human cancers, including the stomach, as compared with matching non-cancerous tissue [19].miR-21 is also an oncogenic miRNA that can modulate the expression of multiple tumour suppressor genes, such as phosphatase and tensin homolog (PTEN), Serpini1, and programmed cell death 4 protein (PDCD4) [20,21].…”
Section: Introductionmentioning
confidence: 99%